(3cJGH TQM COH GdbVGAs - (3CHh SYO eMeO Hf CMeO Hf CHi jhSa GdgQhis; (3YHjO Gddg Hf eSYhO Hf eMehO Hf CMeO GdeMHhHj GdHNGQj GdMfaj, UOQ GdTQjYIs ((3eMeO Hf CMeO GdYHGOi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf bGd GdbGVi GdGhMO CHh SYjO eMeO Hf CMeO Hf CHj jhSa YQV Ydi HYV GNhGfi eLehYkG dCSJGPi GdGeGe CHj YGUe eMeO Hf CMeO GdYdGFi QMeg Gddg ai GOH GdbVGA s
(3BNQgG (B:s
(3hLO GdGLjQ GdeTJQc ef jYed dg hdZjQg hdjS JMJ jO UGMHg hbjd Cf Jbhd CaYd ceG JQi hdG jYjf dg ehVhYkG hGddg GYde Je GdcJGH HMeO Gddg hefg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B103s
Keywords: (3Gdabg GdESdGejs